STUDI KOMPARASA ANTARA MODEL PEMBELAJARAN TALKING STICK DENGAN MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA SWASTA TAMANSISWA PEMATANGSIANTAR T.A. 2022/2023 - Sihombing, Sotarduga; Meyana Sitorus, Debbi Petra (Penerbit Widina, Widina Media Utama, 2021)
This research aims to determine the difference between the talking stick learning model and the make a match learning model on student learning outcomes in economics subjects on economic issues in the economic system of class This research is quantitative in type. The research approach used was quasi-experimental with a posttest only design research design. The sampling technique in this research was a simple random sampling technique with a sample of two experimental classes, each consisting of 30 students or a total sample of 60 students in class X Tamansiswa Private High School Pematangsiantar. Data collection techniques using tests, observation and documentation. The data obtained is in the form of student learning outcomes data. The instrument used is a test of student learning outcomes. The hypothesis test used is the independent sample t test. The results of the research show that there is a difference between the talking stick learning model and the make a match learning model on student learning outcomes, this is indicated by the value, tcount of 3.595. So it can be seen that the value of tcount ttable (3.595 1.671) means that the alternative hypothesis is accepted. The Talking stick learning model obtained an average value of 62.16, while the application of the make a match learning model obtained an average value of 72.67. So the difference in student learning outcomes from the two experimental classes is 11. It is recommended that the results of this research can be used to develop learning systems in schools.ABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan antara model pembelajaran talking stick dengan model pembelajaran make a match terhadap hasil belajar siswa pada mata pelajaran ekonomi materi masalah ekonomi dalam sistem ekonomi kelas X SMA Swasta Tamansiswa Pematangsiantar Tahun Ajaran 2022/2023. Penelitian ini berjenis kuantitatif. Pendekatan penelitian yang digunakan adalah quasi eksperimental dengan rancangan penelitian posstest only design. Teknik pengambilan sampel dalam penelitian ini adalah teknik simple random sampling dengan sampel dua kelas eksperimen yang masing-masing berjumlah 30 siswa atau total sampel berjumlah 60 siswa kelas X SMA Swasta Tamansiswa Pematangsiantar. Teknik pengumpulan data dengan menggunakan tes, observasi dan dokumentasi. Data yang diperoleh berupa data hasil belajar siswa. Instrument yang digunakan adalah tes hasil belajar siswa. Uji hipotesis yang digunakan adalah uji t sampel independen. Hasil penelitian menunjukkan bahwa ada perbedaan Antara model pembelajaran talking stick dengan model pembelajaran make a match terhadap hasil belajar siswa hal ini ditunjukkan dengan nilai, thitung sebesar 3,595. Maka dapat diketahui bahwa nilai thitung ttabel (3,595 1,671) artinya hipotesis alternative diterima. Model pembelajaran Talking stick memperoleh nilai rata-rata 62,16 sedangkan penerapan model pembelajaran make a match memperoleh nilai rata-rata 72,67. Maka selisih nilai hasil belajar siswa dari kedua kelas eksperimen adalah 11. Disarankan agar hasil penelitian ini dapat dipakai dalam rangka mengembangkan sistem pembelajaran di sekolah.